Multimodal Quality of Life Assessment in Post-9/11 Veterans With Epilepsy: Impact of Drug Resistance, Traumatic Brain Injury, and Comorbidity. (26th April 2022) - Gugger, James J.; Kennedy, Eamonn; Panahi, Samin; Tate, David F.; Roghani, Ali; Van Cott, Anne C.; Lopez, M. Raquel; Altalib, Hamada; Diaz-Arrastia, Ramon; Pugh, Mary Jo
Abstract : Background and Objectives: Epilepsy is defined by the occurrence of multiple unprovoked seizures, but quality of life (QOL) in people with epilepsy is determined by multiple factors, in which psychiatric comorbid conditions play a pivotal role. Therefore, understanding the interplay between comorbid conditions and QOL across epilepsy phenotypes is an important step toward improved outcomes. Here, we report the impact of QOL across distinct epilepsy phenotypes in a cohort of post-9/11 veterans with high rates of traumatic brain injury (TBI). Methods: This observational cohort study from the Veterans Health Administration included post-9/11 veterans with epilepsy. A process integrating an epilepsy identification algorithm, chart abstraction, and self-reported measures was used to classify patients into 1 of 4 groups: (1) epilepsy controlled with medications, (2) drug-resistant epilepsy (DRE), (3) posttraumatic epilepsy (PTE), or (4) drug-resistant PTE (PT-DRE). Summary scores for 6 QOL measures were compared across the groups after adjustment for age, sex, and number of comorbid conditions. Results: A total of 529 survey respondents with epilepsy were included in the analysis: 249 controls (i.e., epilepsy without DRE or PTE), 124 with DRE, 86 with PTE, and 70 with PT-DRE. DRE was more common in those with PTE compared with those with nontraumatic epilepsy (45% vs 33%, odds ratio 1.6 [95% CI 1.1–2.4], p = 0.01). Patients with PTE and PT-DRE had significantly more comorbid conditions in health records than those with nontraumatic epilepsy. Those with both PTE and DRE reported the lowest QOL across all 6 measures, and this persisted after adjustment for comorbid conditions and in further linear analyses. Discussion: Among those with PTE, DRE prevalence was significantly higher than prevalence of nontraumatic epilepsies. PTE was also associated with higher burden of comorbidity and worse overall QOL compared to nontraumatic epilepsies. People with PTE are distinctly vulnerable to the comorbid conditions associated with TBI and epilepsy. This at-risk group should be the focus of future studies aimed at elucidating the factors associated with adverse health outcomes and developing antiepileptogenic therapies.